Puzzle: A Christmas Story (Shenden, Guangdong, China : Aquarius)
A CHRISTMAS STORY PUZZLE: This double sided shaped 600 piece jigsaw puzzle features the Leg Lamp from A Christmas Story, one of the most iconic and recognizable movie props of all time. The completed puzzle measures 13 x 30 inches
14 years and up